2007
DOI: 10.1002/ccd.20874
|View full text |Cite
|
Sign up to set email alerts
|

The impact of renal function on the long‐term clinical course of patients who underwent percutaneous coronary intervention

Abstract: The level of renal function is a strong determinant of long-term all-cause and cardiac mortality after successful PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 54 publications
2
2
0
Order By: Relevance
“…33 However, some earlier reports indicated that there was no difference in the repeat revascularization rate between the chronic kidney disease group and the normal renal function group. 34,35 In this study, the rates of TLR were also similar among the four subgroups despite the reduced renal function. There are some probable explanations.…”
Section: Clinical Outcomessupporting
confidence: 60%
“…33 However, some earlier reports indicated that there was no difference in the repeat revascularization rate between the chronic kidney disease group and the normal renal function group. 34,35 In this study, the rates of TLR were also similar among the four subgroups despite the reduced renal function. There are some probable explanations.…”
Section: Clinical Outcomessupporting
confidence: 60%
“…Among a relatively large, representative cohort of patients with ESRD treated with PCI using DES, long‐term freedom from MACE and survival were generally poor compared with matched control patients without ESRD. Nearly two‐thirds of ESRD patients experienced MACE and less than half of ESRD patients survived 3 years after PCI with DES, a finding consistent with prior studies 9,16‐19 . We developed risk models for both MACE and mortality among patients with ESRD undergoing PCI, both with good predictive capacity (C‐indices of 0.65 and 0.66, respectively).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, renal insufficiency is an independent predictor of increased in-hospital morbidity and mortality after PCI with stent implantation (33). Even after successful PCI, CKD was associated with increased short-term and long-term mortality (19, 34). According to our data and those of others, eGFR is a strong prognostic marker independent of underlying severity of CAD in patients with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%